(untitled) (BIRDEM Medical Journal, 2017)
Background: Diabetes and leprosy are chronic conditions for which patients need to practise self-care. Little is known about how patients manage such comorbidities in Bangladesh. Methods: Leprosy disabled people in north-west Bangladesh were surveyed for diabetes. Random blood glucose levels were measured. Data on disability levels and body mass index were collected and diabetic subjects were interviewed about self-care for their disease. Results: Of the 3573 people with leprosy-related disability surveyed, 97(2.7%) were previously diagnosed with diabetes. They were variously receiving treatment and advice from specialist clinic services or other sources; 65% were on regular medication and only 16% were attending clinic for review more frequently than once in 3 months. Other patients were not receiving regular treatment or medical attention for their diabetes. A random blood glucose done by finger prick test showed 51/97 had levels >11.0 mmol/l and 20/97 had levels >18.0 mmol/l. Their self-reported compliance with medical advice was low. Amongst leprosy-disabled people, not previously known to be diabetic, with random blood glucose >11.0 mmol/l, referred for further assessment. Another 47 cases were confirmed to have diabetes making total prevalence about 4% in this population. Conclusions: The survey results suggest that routine screening for diabetes amongst people affected by leprosy should be considered and that special attention needs to be directed to the ability and motivation of people with leprosy related disability to manage their own diabetes self-care. Birdem Med J 2016; 6(2): 100-106